MODEL PENGEMBANGAN TEKNIK ASSERTIVE TRAINING DENGAN RATIONAL EMOTIVE BEHAVIOR THERAPY (SIGNATORY) TERHADAP PENINGKATAN KEPERCAYAAN DIRI ANAK DI PSAA NUGRAHA KOTA BANDUNG - AFDALIA DAMARA EKASANDI; Milly Mildawati; Bambang Rustanto (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
Technique Development with Rational Emotive Behavior Therapy (REBT) is the result of psychosocial therapy technology engineering in the form of combining Assertive Training techniques with Rational Emotive Behavior Therapy (REBT) to increase children's self- confidence. The addition of the Rational Emotive Behavior Therapy (REBT) model aims to reduce client cognitive distortions so that there is an increase in self-confidence due to positive thinking and attitude. This study aims to explain the results of the implementation of the development of Assertive Training techniques with Rational Emotive Behavior Therapy (REBT) to increase children's self-confidence. This research uses a quantitative approach with Single Subject Design (SSD) type of A-B-A reversal. The subjects in the study were FT and IM. The target behaviors observed in this study are resilient in facing difficulties, doing tasks, expressing opinions or questions and maintaining concentration. The validity test of the measuring instrument uses face validity, while the reliability test uses percent agreement. The data analysis used is a visual analysis consisting of analysis within conditions and between conditions. The interim research results show that during the intervention or treatment has an influence in increasing children's self-confidence. The number of frequencies and durations shows an increase, then the direction of the graph goes up and the level changes between conditions which shows the meaning of improving. Researchers are currently still measuring the second baseline condition (A2) as a control for intervention conditions. Keywords: Development of Assertive Training Techniques with REBT, Children with Low Self- Confidence.